Legal Certainty and Evidentiary Strength of Digital Signatures in Electronic Contracts under Indonesian Law - Syahmi, Taffy Faiq; Agus Wardhono; Borman, M. Syahrul; Prawesthi, Wahyu (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2026)
The rapid advancement of digital technology has driven the widespread use of electronic contracts in modern business transactions, where digital signatures play an essential role in verifying authenticity, maintaining document integrity, and establishing mutual consent between parties. This study analyzes the legal validity and evidentiary weight of digital signatures under Indonesian law. Using a normative juridical approach, it examines relevant laws, particularly Law No. 11 of 2008 as amended by Law No. 19 of 2016 on Electronic Information and Transactions (ITE Law), along with supporting regulations and legal literature. The research evaluates whether digital signatures meet legal requirements and provide certainty in practice. The findings show that digital signatures are legally valid and binding if they can identify the signer, maintain document integrity, and prevent repudiation. They are also recognized as legitimate evidence in court. However, challenges remain, including limited public understanding, the need for stronger technological security, and the continued use of handwritten signatures for certain documents. Overall, digital signatures enhance the reliability of electronic contracts and support secure digital transactions in Indonesia.